To solve the questions based on the table provided, we first need to analyze the relationship between the ages of the cat (c) and the dog (d).
From the data in the table:
- When c = 1, d = 4
- When c = 2, d = 5
- When c = 3, d = 6
- When c = 4, d = 7
We can observe that for each year the cat ages by 1 year, the dog ages by 1 year as well. However, the dog is always 3 years older than the cat.
Question 1
To express this relationship mathematically, since the dog is 3 years older than the cat, we can formulate the equation:
\( d = c + 3 \)
So the correct answer is:
D: d = c + 3
Question 2
If we want to find the age of Jamie's dog when her cat is 7 years old, we can use the established equation \( d = c + 3 \):
Substituting \( c = 7 \): \[ d = 7 + 3 = 10 \]
Thus, the age of Jamie's dog when her cat is 7 years old is:
B: 10